(untitled) (Economic and Political Thought, 2018)
For more than 20 years, a principle of taxation of goods and services in the state of destination has been in force in the European Union – VAT is levied according to the rate applied in the state of the purchaser of goods. The principle was introduced due to, inter alia, the differences in the VAT rates in individual Member States, and was planned to operate temporarily, especially until the VAT rates harmonisation process is completed. The intended “definitive” VAT regime was based on the principle of taxation in the Member State of origin, i.e. at the rate applicable in the country of the supplier. The recently published Commission Communication announced several actions towards the change in the rules on taxation of the cross- -border transactions so that the suppliers could levy VAT on the purchasers similarly as it happens in case of domestic transactions, i.e. in accordance with the rates applicable in the state of destination of goods. The Article aims to present the general conclusions on the results of the research into the need to harmonize the rates, particularly in the light of the latest plans of the Commission.